Assessing the Impact of Aeolus Wind Profiles in WRF-Chem Model Dust Simulations in September 2021 - Eleni Drakaki; Vassilis Amiridis; Antonis Gkikas; Eleni Marinou; Emmanouil Proestakis; Georgios Papangelis; Angela Benedetti; Michael Rennie; Christian Retscher; Demetri Bouris; Petros Katsafados (Environmental Sciences Proceedings, 2023)
Windblown dust plays a crucial role in the Earth system, impacting climate, ecosystems, human activities, and health. The spatiotemporal evolution of dust plumes during transport is determined by wind, the primary driver of dust emission. In this study, we utilize outputs from the ECMWF-IFS, assimilating quality-assured Aeolus wind profiles, to initialize dust simulations with the WRF-Chem model. The aim is to assess the impact of Aeolus wind observations on modeling the desert dust cycle. Focusing on the ASKOS/JATAC campaign in September 2021 near Cabo Verde, we qualitatively and quantitatively evaluate the simulated dust-related outputs, revealing that even small differences in wind significantly affect the simulated dust emission rates and dust optical depth.